Neonatal Pressure Controlled and Guaranteed Volume Ventilation - I. I. Afukov; S. M. Stepanenko; V. A. Mikhelson (Общая реаниматология, 2005)
Objective. To comparatively analyze pressure controlled ventilation (PCV) and pressure controlled and guaranteed vol3 ume ventilation (VAPS) in the postoperative period. 26 neonatal infants with various surgical diseases treated at the intensive care unit, N. F. Filatov City Clinical Hospital 13, were examined. According to the type of artificial ventilation (AV), the patients were divided into 2 equal groups. Groups 1 and 2 infants received VAPS and PCV, respectively.The results indicated that for normal gas exchange, less oxygen concentrations may be used during VAPS than during PCV. The mean airways pressure during VAPS that provides adequate ventilation and satisfactory gas exchange is noticeably less than that during PCV.